The Role of Islamic Religious Education Teachers in Shaping Students' Religious Awareness at Muara Kulam State Junior High School, Ulu Rawas District, North Musi Rawas Regency - Fadia Cempaka; Najmul Hayat (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aims to examine the role of Islamic Education (PAI) teachers, the strategies employed, and the supporting and inhibiting factors in shaping students’ religious awareness at SMP Negeri Muara Kulam. This research uses a qualitative method with a descriptive approach, employing observation, interviews, and documentation techniques. The findings reveal that PAI teachers play a strategic role as educators, mentors, role models, and motivators in instilling religious values. The strategies include habituation of worship practices, exemplary behavior, moral advice, and integration of religious values into learning activities. Supporting factors include a conducive religious school environment and collaboration among stakeholders, while inhibiting factors involve low student motivation, external environmental influences, and lack of self-awareness. It is concluded that developing students’ religious awareness requires synergy between teachers, schools, families, and the social environment.